2018
DOI: 10.1016/j.jtumed.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the standard physiotherapy programme on pain and isokinetic ankle strength in individuals with grade I ankle sprain

Abstract: Objectives The isokinetic evaluation of the ankle joint is important in determining the effectiveness of the rehabilitation programme for the management of ankle sprains. This study aimed to determine the effects of physiotherapy programme on isokinetic variables in individuals with grade I ankle sprains. Methods Seven patients with acute grade 1 ankle sprain (15 days of ankle sprain) were recruited. They were provided with 7 days of protection, optimal loading, ice, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
10
0
3
Order By: Relevance
“…Brent et al reported that ankle invertor and evertor strength was significantly increased in college students with CAI after a 6-week strength training program [ 49 ]. Mohd Salim et al also observed that the ankle eversion/inversion strength ratio improved in the ankles of patients with CAI after a 1-week standard physiotherapy program [ 51 ]. These studies suggest that ankle eversion or inversion strength in the ankles of patients with CAI could be increased compared with those with healthy ankles after specific exercise training for mitigating CAI [ 49 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brent et al reported that ankle invertor and evertor strength was significantly increased in college students with CAI after a 6-week strength training program [ 49 ]. Mohd Salim et al also observed that the ankle eversion/inversion strength ratio improved in the ankles of patients with CAI after a 1-week standard physiotherapy program [ 51 ]. These studies suggest that ankle eversion or inversion strength in the ankles of patients with CAI could be increased compared with those with healthy ankles after specific exercise training for mitigating CAI [ 49 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mohd Salim et al also observed that the ankle eversion/inversion strength ratio improved in the ankles of patients with CAI after a 1-week standard physiotherapy program [ 51 ]. These studies suggest that ankle eversion or inversion strength in the ankles of patients with CAI could be increased compared with those with healthy ankles after specific exercise training for mitigating CAI [ 49 , 51 ]. However, we are the first to further examine the ECC and CON of eversion and inversion strengths at various angular velocities and compare training and nontraining groups in the context of the ankles of patients with CAI.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our results, where of the 213 clinics examined only 120 had rehabilitation data for lateral ligament injuries available. Green et al also mentioned that the majority of the rehabilitation protocols are out of date, although recommendations for specific steps for the early rehabilitation after lateral ligament injuries of the ankle have been published recently (Chen et al, 2019; Doherty et al, 2017; Keene, Williamson, Bruce, Willett, & Lamb, 2014; Mohd Salim, Umar, & Shaharudin, 2018; van den Bekerom et al, 2013; Vuurberg et al, 2018). However, these recommendations might not have been employed into clinical practice yet and therefore were not sufficiently implemented in our evaluated rehabilitation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation is crucial for adequate therapy. For example, a grade III ligament lesion requires a more cautious therapy than a grade I lesion (Brison et al, 2016; Mohd Salim et al, 2018; Scillia et al, 2017). Further protocols are needed with an individual therapy that refers to the severity of the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions such as neuromuscular training and balance exercises have demonstrated effectiveness in dealing with deficiencies in muscle strength. The strength training of weakened muscles is vital for prompt recovery and acts as a preventive measure against future injuries [ 9 ]. The typical approach to treating SIJ dysfunction through physical therapy focuses on addressing the abdomino-lumbo-sacro-pelvic-hip complex.…”
Section: Introductionmentioning
confidence: 99%